Pengembangan LKPD Melalui Video Interaktif Materi Peristiwa Sekitar Proklamasi dengan Penguatan Karakter Semangat Kebangsaan Kelas V SDN - Riza Rizky; M. Zainuddin; Sri Murdiyah (Universitas Negeri Malang, 2022)
Abstract: LKPD is one type of teaching material that has an important role in learning, the LKPD function is that it can facilitate students in understanding the material and increase learning activities, both done individually and in groups. This research development aims to test the feasibility of LKPD through interactive videos in terms of validity and practicality. The research method used is Dick and Carey which includes 10 stages: 1) analyzing the needs to identify learning objectives, 2) analyzing learning, 3) analyzing learners and their context, 4) writing performance objectives, 5) developing assessment instruments, 6) developing assessment instruments, learning strategies, 7) developing and selecting learning materials, 8) designing and implementing formative evaluations, 9) revising learning, and 10) designing and implementing summative evaluations. The results of the research and development of LKPD through interactive video showed the validity level of the material expert validation was 96.8 percent, the media expert validation was 96.8 percent, the user/teacher validation was 100 percent, so the LKPD through interactive video included teaching materials in the very valid category. The results of trials in the field show that the practicality of the students is 97.5 percent with a very practical category and can be used in learning in the fifth grade of elementary school, coupled with the appearance of LKPD and interesting videos that make students' learning interest increase. Abstrak: LKPD merupakan salah satu jenis bahan ajar yang mempunyai peran penting dalam pembelajaran. Fungsi LKPD yaitu dapat mempermudah peserta didik dalam memahami materi dan meningkatkan aktivitas belajar, baik dilakukan secara individu maupun kelompok. Penelitian pengembangan ini memiliki tujuan untuk menguji kelayakan LKPD melalui video interaktif dari segi kevalidan dan kepraktisan. Metode penelitian yang digunakan adalah Dick dan Carey yang meliputi 10 tahap yaitu 1) menganalisis kebutuhan untuk mengidentifikasi tujuan pembelajaran, 2) menganalisis pembelajaran, 3) menganalisis pebelajar dan konteksnya, 4) menuliskan tujuan unjuk kerja, 5) mengembangkan instrumen penilaian, 6) mengembangkan strategi pembelajaran, 7) mengembangkan dan memilih bahan pembelajaran, 8) merancang dan melaksanakan evaluasi formatif, 9) merevisi pembelajaran, dan 10) merancang dan melaksanakan evaluasi sumatif. Hasil penelitian dan pengembangan LKPD melalui video interaktif menunjukkan tingkat kevalidan dari validasi ahli materi sebesar 96,8 persen, validasi ahli media sebesar 96,8 persen, validasi pengguna/ guru sebesar 100 persen, sehingga LKPD melalui video ineraktif termasuk bahan ajar dengan kategori sangat valid. Hasil uji coba produk di lapangan menunjukkan tingkat kepraktisan dari peserta didik sebesar 97,5 persen dengan kategori sangat praktis dan dapat digunakan dalam pembelajaran di kelas V SD, ditambah dengan tampilan LKPD dan video yang menarik membuat minat belajar peserta didik meningkat.